Corrective exercises for recognizing underlying structures in sentence comprehension - Valdez, Esmeralda Edralin 1940-
This study presents corrective exercises which will strengthen structural comprehension of the sentence unit in reading English as a second language. These work-type exercises are intended for students who have not acquired the ability to read by structural unit as the unit of meaning. Different types of exercises have been made for Unit I to Unit IV.